2022
DOI: 10.3390/jcm11236987
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-MET in Estrogen Receptor Positive and HER2 Negative Resected Breast Cancer Correlated with a Poor Prognosis

Abstract: Introduction: The mesenchymal-epithelial transition factor (c-MET) receptor is overexpressed in about 14–54% of invasive breast cancers, but its prognostic value in clinical practice is still unclear. Methods: In order to investigate the relationship between c-MET expression levels and prognosis, we retrospectively reviewed the clinical features and outcomes of 105 women with estrogen receptor positive HER2 negative (ER+/HER2-) resected breast cancer. We used the Kaplan Meier method to estimate Disease Free Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…BC is common in women and innovative technologies for very accurate diagnosis and treatments were established (24)(25)(26) while male breast cancer is rare, and CUP of male breast origin is anecdotal. Moreover, there is no consensus in literature about a specific panel of IHC due to their rarity (27).…”
Section: Discussionmentioning
confidence: 99%
“…BC is common in women and innovative technologies for very accurate diagnosis and treatments were established (24)(25)(26) while male breast cancer is rare, and CUP of male breast origin is anecdotal. Moreover, there is no consensus in literature about a specific panel of IHC due to their rarity (27).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrations in c-MET have been described among several potential mechanisms of resistance to CDK4/6is (60). Increased c-MET expression, frequently observed in HR + /HER2breast cancer (61,62), is associated with disease stage, progesterone receptor levels, Ki67 index and worse survival (63).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 6010 breast cancer cases indicated the association between MET overexpression and poor relapse-free survival in hormone receptor-positive disease [11]. Also, in patients with ER-positive/HER2-negative early breast cancer, high MET expression correlated with poor survival outcomes, suggesting its prognostic impact in patients with hormone-dependent tumors [20]. Previous data demonstrated that the overexpression of MET induced resistance to endocrine drug fulvestrant in breast cancer cell lines, an efect that was further associated with increased cancer cell migration and invasion [21].…”
Section: Introductionmentioning
confidence: 99%